Journal of Spacecraft and Rockets: a Scientometric Analysis - Aswathy, S; Gopikuttan, A. (Journal of Information and Knowledge, 2012)
Journal of Spacecraft and Rockets is one of the premier journals in the field of Space technology. It is published by American Institute of Aeronautics and Astronautics. This paper presents bibliometric analysis of the journal during 2006-2010 which includes 780 papers and 15648 references. The analysis covers various parameters like growth pattern, authorship patterns, and distributions with regard to subject, year, institution and geographical area. The citing pattern of authors is also analysed from the reference provided for each article. It is also analysed to know the most productive year. Length-wise analysis of articles is also carried out. The study also reveals the degree of collaboration among the authors and Lotka‟s law is also applied to find the author productivity. The major finding of the study is that universities are the most productive sector and that the most productive country is USA.